Réponses

2014-03-25T17:17:13+01:00
Bonjour,

\dfrac{3x(2x+1)}{x+2}\le x\\\\\dfrac{3x(2x+1)}{x+2}-x\le 0\\\\\dfrac{3x(2x+1)}{x+2}-\dfrac{x(x+2)}{x+2}\le 0\\\\\dfrac{3x(2x+1)-x(x+2)}{x+2}\le 0\\\\\dfrac{6x^2+3x-x^2-2x}{x+2}\le 0\\\\\dfrac{5x^2+x}{x+2}\le 0\\\\\dfrac{x(5x+1)}{x+2}\le 0

Tableau de signes.

Racines : Numérateur : x = 0
                                  5x + 1 = 0 ==> 5x = -1
                                                  ==> x = -1/5
               Dénominateur : x + 2 = 0 ===> x = -2

\begin{array}{|c|ccccccccc||}x&-\infty&&-2&&-\dfrac{1}{5}&&0}&&+\infty\\ x&&-&-&-&-&-&0&+&\\ 5x+1&&-&-&-&0&+&+&+&\\x+2&&-&0&+&+&+&+&+&\\Quotient&&-&|&+ &0&-&0&+&\\\end{array}\\\\\\S=]-\infty;-2[\ \cup\ [-\dfrac{1}{5};0]
Hiphigenie Meeeerci beaucoup
Avec plaisir :)